Interagency-aviation industry collaboration on planning for pandemic outbreaks : summary of a workshop - Turnbull, Katherine F.; National Research Council (U.S.). Transportation Research Board; Airport Cooperative Research Program (Washington, D.C. : Transportation Research Board, 2008)
In September 2007, approximately 70 people assembled in Washington, D.C., to participate in a workshop on Interagency Aviation Industry Collaboration on Planning for Pandemic Outbreaks. The conference brought together individuals involved in planning and responding to pandemic events from both the public sector (federal agencies and state and local agencies, including public airports) and the private sector (airlines and consultants with expertise in various facets of aviation). The workshop goals were to examine (a) the action items included in the section on Transportation and Borders in the May 2006 National Pandemic Plan that directly or indirectly affect air transportation, (b) the current state of the practice for pandemic planning by airports and airlines, (c) coordination among various agencies and the aviation sector to implement these plans, and (d) potential areas for public private sector cooperation in pandemic planning. To plan the workshop, TRB assembled a committee appointed by the National Research Council to organize and develop the workshop program.
Workshop held September 5-7, 2007, Washington, D.C., and sponsored by Airport Cooperative Research Program, Transportation Research Board.
Includes bibliographical references (pages 31-33).
Keywords: Air travel -- Health aspects -- United States -- Congresses; Air travel -- United States -- Planning -- Congresses; Aeronautics -- Health aspects -- United States -- Congresses; Epidemics -- United States -- Prevention -- Congresses; Communicable diseases -- United States -- Prevention -- Congresses; Bioterrorism -- United States -- Prevention -- Congresses; Aeronautics -- United States -- Planning -- Congresses